2015
DOI: 10.1371/journal.pone.0121489
|View full text |Cite
|
Sign up to set email alerts
|

Compound Heterozygous Mutation of Rag1 Leading to Omenn Syndrome

Abstract: Omenn syndrome is a primary immunodeficiency disorder, featuring susceptibility to infections and autoreactive T cells and resulting from defective genomic rearrangement of genes for the T cell and B cell receptors. The most frequent etiologies are hypomorphic mutations in “non-core” regions of the Rag1 or Rag2 genes, the protein products of which are critical members of the cellular apparatus for V(D)J recombination. In this report, we describe an infant with Omenn syndrome with a previously unreported termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…The second one leads an amino acid change (glutamic acid to lysine) in the core domain of RAG1 which is essential for V(D)J recombination. 11,12 In patient 2, T-B-NK+ SCID, we found a novel, nonsense c.581C > A variant (CADD: 36) in RAG2 gene. The homozygous single-nucleotide variant leads a premature stop codon instead of serine at conserved amino acid position 194 (Fig.…”
Section: Exome Sequencingmentioning
confidence: 83%
See 1 more Smart Citation
“…The second one leads an amino acid change (glutamic acid to lysine) in the core domain of RAG1 which is essential for V(D)J recombination. 11,12 In patient 2, T-B-NK+ SCID, we found a novel, nonsense c.581C > A variant (CADD: 36) in RAG2 gene. The homozygous single-nucleotide variant leads a premature stop codon instead of serine at conserved amino acid position 194 (Fig.…”
Section: Exome Sequencingmentioning
confidence: 83%
“…2b). 11,12 This variant has not been published before. The second one leads an amino acid change (glutamic acid to lysine) in the core domain of RAG1 which is essential for V(D)J recombination.…”
Section: Exome Sequencingmentioning
confidence: 99%
“…The first missense variant causes an amino acid change of arginine to glycine. It affects the B1 basic domain of the protein which serves as binding site for the nuclear transport proteins . The second missense variant leads to an alanine‐to‐valine change which was in the nanomer DNA‐binding region of the protein , (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…c.256-257del and c.C1331T, in RAG1. Matthews et al (15) reported a boy with OS bearing compound heterozygous mutations of RAG1.…”
Section: Discussionmentioning
confidence: 99%